Framework for Interior Design Work Development Plan (IDWDP) in Malaysian context / Arniatul Aiza Mustapha - Mustapha, Arniatul Aiza (2019)
The works of an interior designer in managing interior design projects have been recognized as similar as an architect, as well as the work processes. The interior designer takes part on theme an ideal space, and the architect addressing the theme for the buildings as well as general spatial layout. Particularly, the scope and process in interior project delivery conducted by interior designer has frequently been argued on lacking of standard of scope of work, which was raised disputes amongst the team players, on the work coordination, process and flow. Initially, in searching to address this issue, this research was undertaken to confirm the arguments and to develop a management framework for interior designer in managing interior design projects. The argument was on to what extent is the existence of standard work development plan, and what are the definite needs of scope of work for interior design project delivery, the processes, flow, gaps, and work elements of each work stages. A qualitative research methodology was employing for the research. A preliminary investigation has been executed amongst the interior design project team players including the interior designers themselves. A scrupulous content analysis from a written documents collected was executed verbatim, to set up for a data base. Sets of interviews amongst twelve key respondents for twenty current ongoing and completed projects to record the work flow, processes and scopes. The interior design framework was employed and tested to a selected interor design work development process framework to identify the gaps of the work flow and process of interior design project delivery. The findings found significant gaps in the current interior design project delivery practices which this is closely related to the issue stated, the non existence of appropriate written standard documents of plan of work for interior design project delivery practice. Significant of new knowledge related to the interior design projects delivery was identified through this research, where with this framework, the interior projects delivery process can be improvised.